Whole exome sequencing reveals pathogenic variants in CNGA3, CACNA1F, and RPGRIP1 in consanguineous Pakistani families with diverse retinal phenotypes - Jahangir Khan Tareen; Hamid Khan; Shamsul Ghani; Saeed Khan; Bakhtawar Khan; Yurong Wu; Muhammad Ajmal Khan; Syed Shahab Ud Din Shah; Abrar Hussain; Mubin Mustafa Kiyani; Shahid Bashir; Atta Ur Rehman; et al. (PLoS ONE, 2025)
This study investigates the genetic basis of retinal diseases in four consanguineous families from Pakistan, focusing on mutations in the CNGA3, CACNA1F, and RPGRIP1 genes that are implicated in retinal dysfunctions such as achromatopsia, congenital stationary night blindness, and retinal dystrophies. We identified pathogenic variants in these genes, including the novel missense mutation c.955T > C; p.Cys319Arg in CNGA3 (Family 1), the frameshift mutation c.1443dupT; p.Ile482Hisfs*6 in CNGA3 (Family 2), the missense mutation c.2254G > A; p.Val752Met in CACNA1F (Family 3), and the frameshift mutation c.2789dupT; p.Pro931Thrfs*3 in RPGRIP1 (Family 4). Clinical features associated with these mutations include nystagmus, photophobia, reduced visual acuity, and color vision deficiency, with some patients progressing to complete blindness. The findings were validated through Sanger sequencing, segregation analysis, and in silico prediction tools. Additionally, molecular dynamics simulations were conducted to assess the impact of the CNGA3 p.Cys319Arg mutation on protein structure, revealing significant alterations in protein conformation and dynamics. These results highlight the significance of CNGA3, CACNA1F, and RPGRIP1 in retinal health and provide valuable insights into the genetic underpinnings of retinal disorders. Our findings contribute to improved genetic counseling, potential targeted therapies, and a deeper understanding of inherited retinal diseases.